The sources of pharmaceuticals for problematic users of benzodiazepines and prescription opioids. Issue 10 (18th November 2013) - Nielsen, Suzanne; Bruno, Raimondo; Degenhardt, Louisa; Stoove, Mark A; Fischer, Jane A; Carruthers, Susan J; Lintzeris, Nicholas
Abstract: Objectives: To describe benzodiazepine and prescription opioid use by clients of drug treatment services and the sources of pharmaceuticals they use. Design: Structured face‐to‐face interviews on unsanctioned use of benzodiazepines and prescription opioids were conducted between January and July 2008. Participants: Convenience sample of treatment entrants who reported regular (an average of ≥ 4 days per week) and unsanctioned use of benzodiazepines and/or prescription opioids over the 4 weeks before treatment entry. Setting: Drug treatment services in Victoria, Queensland, Western Australia and Tasmania. Main outcome measures: Participant demographics, characteristics of recent substance use, substance use trajectories, and sources of pharmaceuticals. Results: Two hundred and four treatment entrants were interviewed. Prescription opioids were predominantly obtained from non‐prescribed sources (78%, 84/108). In contrast, medical practitioners were the main source for benzodiazepines (78%, 113/144). Forging of prescriptions was extremely uncommon. A mean duration of 6.3 years (SD, 6.6 years) for benzodiazepines and 4.4 years (SD, 5.7 years) for prescription opioids was reported between first use and problematic use — a substantial window for intervention. Conclusions: Medical practitioners are an important source of misused pharmaceuticals, but they are not the main source of prescription opioids. This has implications for prescription drug monitoring in Australia: current plans (to monitor only Schedule 8 benzodiazepines and prescription opioids) may have limited effects on prescription opioid users who use non‐prescribed sources, and the omission of most benzodiazepines from monitoring programs may represent a lost opportunity for reducing unsanctioned use of benzodiazepines and associated harm.